Role of Nasal Endoscopy in Initial Management of Epistaxis. - Shamas, Irfan ul (International Journal of Human and Health Sciences (IJHHS), 2019)
Aim: To compare the precision,efficacy and complication of nasal endoscopic assisted management of epistaxis with headlight assisted nasal packing. Materials and Methods: Two groups of twenty patients each were placed randomly in Group A and Group B. Patients in Group A were managed with headlight assisted nasal packing and Group B patients were managed with nasal endoscopic assisted control of epistaxis. Results: Exact site of bleeding was located in 90% patients of Group B. All patients in Group A complained of dry mouth(100%), halitosis in 6 (30%) patients, 12 (60%) patients had headache and discomfort,7(35%) patients had epiphora. There was no complication in Group B. Conclusions: Epistaxis is a common ENT emergency and routine blind hasty nasal packs should be avoided. Nasal endoscopes should be routinely used to identify site of bleeding and cauterisation of the targeted area should be done gently with least collateral damage to healthy mucosa. Good and easy control with less complications and no admissions are all possible with the wonder tool called “ nasal endoscope”. International Journal of Human and Health Sciences Vol. 03 No. 03 July’19. Page: 158-161